EFFECTIVE USE OF INTERACTIVE TECHNIQUES IN THE EDUCATIONAL PROCESS IN PRESCHOOL EDUCATIONAL ORGANIZATIONS (Conferencea, 2022)
The article presents non-traditional approaches to the use of interactive technologies for organizing methodological support for preschool teachers. The essence and purpose of interactive technologies when working with preschool teachers is revealed. Specific examples of the use of interactive technologies with teachers, which are aimed at improving their professional skills, are given. The author is convinced that interactive technologies in the context of methodological work with teachers contribute to increasing creativity and professional competence, providing professional support and creative growth of teachers.